LAYANAN KONSELING KELOMPOK BERBASIS DARING DENGAN PENDEKATAN BEHAVIORAL TERHADAP KEDISIPLINAN PADA SISWA MTS KELAS VII - Arrtika Setiawati; Teti Sobari; Reza Pahlevi (IKIP Siliwangi, 2021)
Discipline is a condition that is created and formed through the process of a series of behaviors that show the values of obedience, obedience, loyalty, order, and order. The purpose of this study is to find out how the implementation of online-based group counseling services on student discipline, student responses and difficulties, as well as the obstacles experienced by BK teachers regarding online-based group counseling services with a behavioral approach. The method used in this research is descriptive qualitative. The data obtained from the research results in the form of words and explanations about a phenomenon that occurs. The subjects in this study were Curriculum Staff, Homeroom Teacher, BK teacher, and class VII MTs Nurul Iman. The data collection procedure uses observation, interview, and documentation techniques. Service implementation in this study was carried out by BK teachers. Students' responses and difficulties to the services provided are different from one another. And there are several obstacles for BK teachers in implementing online group-based counseling services with a behavioral approach. Based on the results of the study, it shows that there are changes experienced by students after participating in online-based group counseling service activities with a behavioral approach. Keywords: : Discipline, Group Counseling, Behavioral Approach